INNOVATION AND PRODUCTION POTENTIAL OF MESOSYSTEMS: ASSESSMENT AND MODELING OF DEVELOPMENT PROSPECTS - Kljushkin , Alexey I.; Shinkevich , Marina V.; Ivanova , Nina A.; Popova , Olga V.; Ryabchenko, Oksana N.; Brykin, Konstantin I. (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the article is due to the fact that the issues of mobilization and effective use of the innovation and production potential of mesosystems are becoming particularly relevant in the context of the deployment of the fourth industrial revolution in the world economic system. The solution of these problems will reveal new opportunities and trajectories of qualitative and quantitative growth of innovative production activity of the industrial complex as a whole. The purpose of the article is, based on the systematization of statistical data on the development trends of the mesosystem, to conduct economic and mathematical modeling, which allows to identify factors of innovative production potential for the formation of their contribution to the development of high- tech and high-tech industrial products. As the main research methods, the article used the description method, which allowed to identify the development trends of mesosystems; the method of correlation analysis, which establishes the closeness of the relationship between the indicators of the use of innovative production potential and the achievement of the level of high technology and high technology production; regression analysis method for constructing economic and mathematical models of the dependence of high-tech production on the use of innovative production potential of the industry. The article describes the production and innovation potential of the mesosystem (for example, industrial complexes); on the basis of the regression model, the negative impact of the innovative potential of industry on the development of high-tech and high technology production was established; The forecast of an increase in the share of high-tech and high-tech products in GDP is constructed. The materials of the article can be used in developing strategies and programs to increase the efficiency of using the innovative production potential of the industrial complex in order to modernize the economic system as a whole.